Enhancing mathematical competence through augmented reality: An exploratory study using best AR in geometry learning - Dewi, Puspita; Harahap, Tua Halomoan; Dachi, Surya Wisada (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
The integration of digital technology in mathematics education holds immense potential to transform abstract concepts into concrete experiences. This study explores the impact of an Augmented Reality (AR)-based learning application, Best AR, on enhancing the mathematical competence of fifth-grade students in Malaysia. Conducted in a tutoring center using an exploratory qualitative approach, the research investigates how the interactive features of Best AR—including 3D object simulations, mini-games, and quizzes—support conceptual understanding, engagement, and problem-solving skills, particularly in learning three-dimensional geometry. Data were collected through interviews, observations, and documentation, and analyzed thematically. The findings reveal that Best AR improved students' ability to visualize and manipulate geometric objects, fostered collaboration, increased motivation, and enhanced logical reasoning. The application’s mobile accessibility and adaptive feedback promoted self-regulated learning, while its gamified elements made mathematics more engaging and enjoyable. Despite challenges in device access and teacher preparedness, the study underscores the potential of AR to bridge gaps in technology integration and enrich mathematics instruction. Implications for curriculum alignment, teacher training, and scalable adoption of AR media in informal learning contexts are discussed.